BURNOUT IN ACADEMIC PHYSICIAN DURING COVID-19 PANDEMIC - Dian Puspita Sari; Yoga Pamungkas Susani; Emmy Amalia (Jurnal Pendidikan Kedokteran Indonesia, 2021)
Background: The COVID-19 pandemic has caused tremendous and abrupt changes in all aspects of social life, including healthcare and education. It has caused stress and psychological impact on physicians and other healthcare workers globally. Exposure to chronic occupational stress can lead to burnout. The multiple responsibilities of academic physicians potentially lead to a higher risk of burnout, particularly during this pandemic. This study aimed to obtain burnout profiles in academic physicians and factors associated with burnout during the COVID-19 pandemic.